Affectivity in teaching activity: reflections from the Clinic of Activity in the context of an inclusive classroom - Clemente, Marina; Moraes , Rozania Maria Alves de; Cruz , Glenda Demes da (The ESPecialist, 2025)
This article analyzes how affections mobilize the teaching activity in an inclusive classroom context. It focuses on the activity of a Spanish language teacher who teaches a group in which there is a student with autism spectrum disorder (ASD). Inserted from the perspective of an Indisciplinary Applied Linguistics (LA), this study is based on the Clinic of Activity studies (Clot, 2006; 2010;2016); in Spinoza’s theory of affects (2019) and in theories that discuss the role of affects in the professional activity (Clot, 2017). This work investigates the teacher’s speech about her activity in a simple self-confrontation, with the aim of understanding how affections influence her pedagogical actions. The methodology used includes self-confrontation, which allows teachers to reflect on their practice and identify affective elements that impact their power to act. The results point to the complexity of managing an inclusive classroom and suggest that affections play an important role in mobilizing the teaching activity, influencing the teachers’ decisions. By analyzing the professional’s discourse, the study contributes to the understanding of the role of affectivity in pedagogical practice and suggests ways to strengthen teachers’ power to act in challenging educational contexts.